THE IMPORTANCE OF FAMILY AND SCHOOL PARTNERSHIP IN THE EDUCATION OF STUDENTS WITH MENTAL DISABILITY - Kholmonova, Mahliyo (Innovative Development in Educational Activities, 2024)
This article highlights the importance of family-school partnerships in the education of students with intellectual disabilities and some modern interactive methods.